Answer:
c=32.13
Step-by-step explanation:
Answer:
y =x² + y² + 2y - 35
Step-by-step explanation:
The equation of a circle is given by the formula;
(x-a)²+(x-b)² = r²
Where; (a, b) is the center of the circle and r is the radius
Therefore;
(x-0)² +(y+1) = 6²
x²+ y² +2y + 1= 36
x² + y² + 2y - 35 = 0
Therefore; The equation of the circle is y = x² + y² + 2y - 35
Answer:
its c
3 : 7
3/7
Step-by-step explanation:
Answer:
159.75
Step-by-step explanation:
23.50×5=117.5
117.5+42.25=159.75
Converting all to improper fractions
31/10s = 31/5
5×31s=31×10
155s = 310
s=310/155= 2
20/9=-4/5m
5×20=-4×9m
100=-36m
m=100/-36 = 72 28/36 = 72 7/9
-14/5=-7/2n
-14×2=5×-7n
-28=-35n
n =-28/-35
n=28/35